Pengaruh Personal Selling, Promosi dan Ketersediaan Produk Terhadap Keputusan Pembelian Handphone Advan PT Maju Telekomunikasi Batam - Jimmy Jimmy; M. Khoiri (Universitas Batanghari, 2023)
This study aims to determine and analyze Personal Selling, Promotion, Product Availability simultaneously influence the purchase decision of PT Maju Telekomunikasi Batam. Forward Telecommunications Batam. The phenomenon of purchasing decisions at PT Maju Telekomunikasi Batam, shows that purchasing decisions experience sales going up and down. This study uses three independent variables, namely personal selling variables, promotion variables, and product availability variables. The method of data collection techniques used in this study was distributing questionnaires using a sampling technique, namely purposive sampling, the number of samples used was 169 people. This study uses data analysis techniques, namely validity, reliability, classical assumption test, multiple linear regression analysis, determinant coefficient test, and hypothesis testing. The results of this study indicate that partially the personal selling variable has a positive and significant influence on purchasing decisions, promotion has a positive and significant influence on purchasing decisions, product availability has a positive and significant influence on decisions, and simultaneously personal selling, promotion, and product availability has a positive and significant influence on purchasing decisions. The variables contained in this study had an influence of 56,7% on purchasing decisions. The remaining 43,3% was influenced by other variables outside this study.